Educación emocional y su incidencia en el rendimiento académico en estudiantes de 6to EGB de la Unidad Educativa “Gabriel García Moreno” periodo 2024 – 2025 - Cordova Mazacon, Ineska Leonela (2025)
Nowadays, emotional education is a key factor in the educational field, because through it, skills are developed that are essential to manage emotions, resolve conflicts and, above all, to maintain an emotional balance in the learning relationship. However, at the “Gabriel García Moreno” School there is the lack of emotional education in sixth-year basic education students. This is why, this research explores how emotional education affects the academic performance of students. Emotional education is fundamental in any educational process, because it contributes to the creation of a more positive classroom environment, where students feel more secure and motivated to learn. In addition, it offers tools to improve their psychological well-being, reduces stress and also for appropriate emotional management. On the other hand, in order to know the level of emotional intelligence on the students, an emotional test carried out on 51 sixth-grade students and as a result, it got that the 76% of students have trouble controlling themselves when they get angry. Affecting their personal well-being and their academic performance. Also, an interview conducted to the institution's principal and to tutor teachers, to analyze in depth these factors that directly affect academic performance. Therefore, it is concluded that the integration of emotional education in the academic curriculum is a key factor to improve academic performance and promote comprehensive development in students.